2023
DOI: 10.1109/access.2023.3299296
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Reservoir Computing and its Interdisciplinary Applications Beyond Traditional Machine Learning

Abstract: Reservoir computing (RC), first applied to temporal signal processing, is a recurrent neural network in which neurons are randomly connected. Once initialized, the connection strengths remain unchanged. Such a simple structure turns RC into a non-linear dynamical system that maps lowdimensional inputs into a high-dimensional space. The model's rich dynamics, linear separability, and memory capacity then enable a simple linear readout to generate adequate responses for various applications. RC spans areas far b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 318 publications
0
3
0
Order By: Relevance
“…[50], it was also demonstrated that the resulting computational scheme does not only circumvent using the matrices of randomly generated neural connections, but is equivalent to and even more computationally efficient than the traditional RC algorithm. This approach was called next-generation reservoir computing [33,[51][52][53][54]. Similar algorithms that further improve the performance of RC systems have also been proposed [55].…”
Section: Next Generation Algorithmic Reservoir Computing and Adjacent...mentioning
confidence: 99%
“…[50], it was also demonstrated that the resulting computational scheme does not only circumvent using the matrices of randomly generated neural connections, but is equivalent to and even more computationally efficient than the traditional RC algorithm. This approach was called next-generation reservoir computing [33,[51][52][53][54]. Similar algorithms that further improve the performance of RC systems have also been proposed [55].…”
Section: Next Generation Algorithmic Reservoir Computing and Adjacent...mentioning
confidence: 99%
“…Liquid State Machine [3] and Echo State Network [4], and later on unified under the name RC [5]. A review about the history and recent developments of RC is given by Zhang et al [6]. Due to their fast data processing and the relatively simple data injection and readout schemes, optical systems are especially suited and a variety of different optical RC implementations have already been proposed, theoretically investigated and experimentally realized [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Reservoir computing (RC) is a resource-efficient neuromorphic information processing algorithm that is especially suitable for making forecasts of highly nonlinear and chaotic time series that underpin a number of essential natural and human-made phenomena, including the variation of climate, dynamics of Earth population, trends in financial markets, energy generation, and drug discovery [12,[20][21][22][23][24][25][26][27]. A typical RC algorithm [20,21] employs a randomly initialised task-dependent neural network (reservoir) that is connected to the input units through random connections.…”
Section: Introductionmentioning
confidence: 99%